From Gélinas to Carrier: Critical Response to Translated Quebec Theatre in Toronto - Koustas, Jane (Studies in Canadian Literature, 1992)
Robert Wallace, in his analysis of critical responses to translated French-Canadian theatre in Toronto, argues that efforts to bridge the cultural gap have sometimes been sabotaged because of a failure to acknowledge, accept, and account for cultural differences. Jane Koustas examines critical responses to translated Quebec theatre in Toronto from 1951 to 1982 and considers general trends through the divergent reviews in the daily press. Particular attention is paid to the critical response to the question of place, as well as the importance attributed to the translation and translator. Michel Tremblay emerges as the most popular Quebec playwright in Toronto, despite the problems of translating his trademark "joual" and the failure of critics to recognize the political and social connotations of his work. As Wallace observes, Toronto institutions either appropriate or dismiss work that is culturally different; in the case of Tremblay, the critical response dismisses the political, Quebec message while appropriating the universal elements.